PERSPEKTIF PEMBELAJARAN KEWIRAUSAHAAN DI PERGURUAN TINGGI DENGAN KONSEP PENDIDIKAN HUMANIS PAULO FREIRE - Novie Kurniasih Kamaruddin; Dewi Amaliah Nafiati (Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
This paper intended to review the humanistic education concept of Paulo Freire according to Entrepreneurship Courses at Indonesian Higher Education. The method used is the content analysis. The paper summarized that Education must be carried out dialogically, not stifling creativity and creativity, because in essence students are not passive beings where the dialogue process itself is a process of awareness as the core of the process of humanization or humanity. In line with the concept of humanization Paulo Freire, the concept of humanization also underpins the entrepreneurship learning process in universities. Entrepreneurship learning is not just learning oriented to business and economics alone, but on exploring values / values of independence, honesty, innovative creative, so that entrepreneurial learning becomes an important learning that is applied in all study programs in higher education. The focus of this article is on entrepreneurship learning in private teacher training colleges which in the main profile print professional teacher candidates and an additional profile that is reliable entrepreneurship printing. Learning entrepreneurship in private teacher training colleges is still said to have not taught the value of humanism. There are several obstacles, among them are still focusing on theoretical with more dominant proportions compared to practice, exploring creative ideas are still dominated by ideas from lecturers so students tend to be passive and less creative, creative idea development programs are not maximally channeled so that it only stops at the completion of the course assignment obligations, the interest and motivation of students to become entrepreneurs has not yet fully arisen by students' self-awareness. Even though the creative ideas that have emerged from students should be continued as a forerunner to the emergence of startup-based young entrepreneurs. Freedom to create ideas and creative thoughts should be extended to students so that students are more motivated and motivated to become job creators than job seekers.